2015
DOI: 10.1016/j.prevetmed.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for short-term marking of domestic dogs for rabies control

Abstract: Rabies transmitted by domestic dogs is a serious yet neglected public health threat in many underserved communities in Africa and Asia. Achieving 70% vaccination coverage in dog populations through annual mass vaccination campaigns is an effective means of controlling the disease in these communities. Evaluating the extent to which this target coverage is achieved requires either accurate pre-campaign estimates of the dog population size or accurate estimates of the coverage attained by conducting post-vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Several authors (5, 13, 72–74) have underlined the importance of a good estimation of the dog population in the success of rabies control programs. According to WHO, the size of the dog population may be estimated through the human:dog ratio (59).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (5, 13, 72–74) have underlined the importance of a good estimation of the dog population in the success of rabies control programs. According to WHO, the size of the dog population may be estimated through the human:dog ratio (59).…”
Section: Resultsmentioning
confidence: 99%
“…Vaccinated dogs are temporarily marked with crayon. Crayon has a short time of persistence (Conan et al 2015b ). Household gates are also marked by drawing a cross with chalk.…”
Section: Methodsmentioning
confidence: 99%
“…Once restrained dogs were vaccinated intramuscularly or subcutaneously (Nobivac® Rabies, MSD Animal Health), marked and released. Vaccinated dogs were marked with non-toxic paint along the top and back of the head to allow for identification on post-vaccination surveys and prevent repeat vaccination [ 16 ]. Vaccination teams continued within the same ward on consecutive days until the vaccination team reported that the maximum number of dogs had been vaccinated, at which time the project manager was informed and a post vaccination survey was undertaken.…”
Section: Methodsmentioning
confidence: 99%